Réformes de structure - Craeybeckx, Lode; Larock, Victor (Bruxelles : Lumière, 1946)
Bibliotheek Camille Huysmans
Dedicator: Craeybeckx, Lode, dedicatee: Anseele (jr.), Edward, dedicatee: Huysmans, Camille
Dedicator: Craeybeckx, Lode, dedicatee: Anseele (jr.), Edward, dedicatee: Huysmans, Camille
Wetsvoorstellen ingediend vanuit socialistische zijde in de eerste maanden na de bevrijding
Frans
Monografie
Keywords: planeconomie